Sharīra Rachana of Pūriṣhavaha Strotas and its Role in the Etiopathogenesis of Ano-Rectal Disorders: An Anatomico-Physiological Review - Dilipkumar Gujrathi, Miteshkumar; Dilip Patil, Sainath; Gulabrao Marathe, Manojkumar (Journal of Science in Medicine and Life, 2026)
Pūriṣhavaha Strotas is one of the important Malavaha Srotasas described in Ayurvedic classics, responsible for formation, transportation, storage, and excretion of pūriṣha (feces). Structural and functional derangement of this srotas plays a pivotal role in the manifestation of various ano-rectal disorders such as Arśha, Bhagandara, Parikartikā, Gudabhramśa, and Vibandha. Śharīra Rachana provides a fundamental understanding of the anatomical framework of Pūriṣhavaha Strotas, which correlates closely with the large intestine, rectum, and anal canal described in modern anatomy. The present article aims to critically review the classical concept, anatomical components, and clinical relevance of Pūriṣhavaha Strotas with special emphasis on its involvement in ano-rectal diseases. Pūriṣhavaha Strotas is a vital excretory channel described in Ayurveda, responsible for formation, storage, and expulsion of pūriṣha. Structural and functional derangement of this strotas leads to a wide spectrum of ano-rectal disorders.